Artefak Religius Yeh Pulu : Mengungkap Peradaban Masyarakat di Indonesia pada Masa Kerajaan Bali - Dimas Julian Pratama; L.R. Retno Susanti; Hudaidah Hudaidah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The goal of this study is to shed light on ancient Bali's inhabitants' way of life and culture. The problem's main objectives are to 1) describe the Yeh Pulu Bedulu relief sculpture's construction and 2) describe the way of life and civilization of the ancient Bali population. 3) What are Ancient Bali's heritage values? 2) To depict the lives and civilization of the people in ancient Bali; 3) To describe and understand the values of the heritage of life and civilization in ancient Bali; and 4) To describe the structure of Yeh Pulu Bedulu relief objects. Benefits include understanding the degree of civilization and existence in ancient Balinese society and its cultural traits. The descriptive qualitative method involves processing and evaluating field data. This study combines the study of structural analysis, topics, processes, and materials with the theory of iconography, ecology, ethnographic approach, and visual language. Data gathering methods include documentation, literature, and observation. Primary and secondary sources of data. Results: using Yeh Pulu relief relics in Bedulu to shed light on the life and civilization of ancient Bali